Systematic Review of Gender- dependent outcomes in sepsis - Papathanassoglou, Elizabeth; Middleton, Nicos; Benbenishty, Julie Sarah; Williams, Ged F.; Christofi, Maria Dolores; Hegadoren, Kathleen Mary (My University, 2017)
Background: Men and women appear to exhibit different susceptibilities to sepsis and possibly divergent outcomes. However, the effect of sex and gender in critical illness outcomes is still controversial and the underlying mechanisms appear to be complex. Objectives: We aimed to systematically review and synthesize evidence on the influence of sex on outcomes in critically ill adult patients with sepsis, as reported in published studies specifically including investigation of the effect of sex among their aims. Primary outcome measures include in-hospital mortality, intensive care unit (ICU) mortality and length of stay (LOS) in the ICU. Search strategy: The review was based on focused literature searches (CINAHL, PUBMED, EMBASE and COCHRANE). Methodological quality was assessed through the STROBE checklist and the Cochrane Tool for Bias in Cohort Studies. Meta-analysis was performed using STATA. Published observational studies addressing outcomes of sepsis among their primary aims and having included gender comparisons among primary outcomes in critically ill adult patients were included. Results: A total of eight eligible studies were included. With the exception of mortality, it was not possible to perform meta-analysis for other outcomes. Included studies reported data on 25,619 patients with sepsis (14309 male/11310 female). There is a paucity of well-designed studies addressing the effect of sex on mortality among patients with sepsis, and absence of studies addressing the effects of sex on multiple organ dysfunction of non-infectious origin. There was significant heterogeneity among study estimates (p=0·001; I2=78·1%). Conclusions: Although results of data syntheses appear to point towards a small disadvantage for survival among women, our results suggest that data on the impact of sex on sepsis outcomes remain equivocal. Implications for future research include approaches to adjustment for confounders and prospective designs. Relevance to clinical practice: Clarifying sex-related differences in sepsis, if any, is crucial for informing evidence-based care.
Keywords: Length of stay; Mortality; Sepsis; Sex; Systematic review